Assembling Nutrition‐sensitive Agriculture: How Global Food Security Projects Are Sustained Despite Tensions, Contradictions and Failure - Seay‐Fleming, Carrie (Development and change, 2025)
This article examines the global discourse surrounding nutrition‐sensitive agriculture (NSA) and its implementation within Feed the Future, a food security initiative of the US Agency for International Development in Guatemala. It explores how such global nutrition efforts have increasingly incorporated critiques advanced by critical nutrition scholars. Employing the analytical concept of ‘practices of assemblage’, the article shows how global nutrition strategies have been assembled, reassembled and maintained through a variety of interconnected practices. It argues that while NSA has facilitated certain politically progressive shifts within global nutrition practices, it simultaneously projects a misleading sense of coherence, obscures historical shortcomings and legitimizes the continuation of nutrition interventions.